Noncoding RNA in Liver Regeneration—From Molecular Mechanisms to Clinical Implications - Sergeeva, Olga; Sviridov, Evgeny; Zatsepin, Timofei (Seminars in Liver Disease, 2020)
The unique ability of the adult liver to regenerate after injury is the basis for efficient surgical resection and liver transplantation and provides solutions for the treatment of liver cancer and acute liver failure. Current success in surgical treatments could be enhanced by directed regulation of liver regeneration. A number of small molecules and growth factors have been tested in mice models to improve liver regeneration. Noncoding ribonucleic acids (ncRNA) are less studied regulators of various cellular processes. Here, the authors carefully review ncRNA involved in liver regeneration and discuss molecular mechanisms and regulatory networks. These ncRNAs modulate the expression of pro- and antiproliferative genes allowing to orchestrate precisely the proliferation of hepatocytes. The authors expect that ncRNA will become new targets in liver regeneration due to recent progress in therapeutic nucleic acids. Among a large number of preclinical studies on ncRNA, only a few entered clinical trials, and further studies are needed to uncover their potential as therapeutic targets.
Keywords: noncoding RNA; liver regeneration; miRNA; lncRNA; therapeutic nucleic acids